Assessment of natural radioactivity and associated radiological risks in selected fish from coast of Terengganu, Malaysia - Muhammad Nur Rashidi Rosli; Mohd Fahmi Mohd Yusof; Nurashikin Abd Azis (Pusat e-pembelajaran, UMS, 2022)
Radionuclide concentrations in seawater and marine organisms are important inputs for assessing radiological impacts on human health and marine ecology. Among the notable radioactive elements are ²³²Th, ²³⁸U, and 40K that were used to determine radiological risk. Since Malaysia is considered among the highest seafood consumers in the Southeast Asian region, it is important to assess the natural radioactivity, particularly in commercial fish coastal such as Terengganu. Herein, using the mentioned radioactive elements, calculation for annual effective dose and cancer risk concentration of radionuclides presence in fish was conducted. The ICP-MS technique was used to determine the levels of natural radionuclide ²³²Th, ²³⁸U and ⁴⁰K in five fish species taken from three locations along the coast of Terengganu, Malaysia. The activity concentration ranges from 63.05 ± 8.65 to 81.21 ± 8.98 for ⁴⁰K, 7.67 × 10⁻³ ± 0.89 × 10⁻³ to 22.50 × 10-4 ± 7.15 × 10-4 for ²³²Th and 1.54 × 10⁻³ ± 0.10 × 10⁻³ to 5.20 × 10⁻³ ± 0.10 × 10⁻³ for ²³⁸U. The results indicated that the annual effective doses (mSv year⁻¹) for ²³²Th, ²³⁸U and ⁴⁰K were estimated to be 1.49 × 10-4, 7.46 × 10-6 and 2.57 × 10⁻²respectively were significantly lower than the UNSCEAR recommendation. Assuming that an individual’s life expectancy is 70 years, the cancer risk factor for adults is projected to be 9.04 × 10⁻⁵ based on the estimated annual effective dose. This number is significantly lower than the UNSCEAR cancer risk factor of 8.4 × 10⁻³ and ICRP cancer risk factor of 3.5 × 10⁻³. The current study suggests that the dose obtained by the locals because of eating fish is relatively low, does not harm human health and is safe for consumption.